Finite-dimensional subalgebras in polynomial Lie algebras of rank one - Arzhantsev, I.V.; Makedonskii, E.A.; Petravchuk, A.P. (Український математичний журнал, 2011)
Let Wn(K) be the Lie algebra of derivations of the polynomial algebra K[X] := K[x1, . . . , xn] over an algebraically closed field K of characteristic zero. A subalgebra L ⊆ Wn(K) is called polynomial if it is a submodule of the K[X]-module Wn(K). We prove that the centralizer of every nonzero element in L is abelian provided that L is of rank one. This fact allows to classify finite-dimensional subalgebras in polynomial Lie algebras of rank one. Нехай Wn(K) — алгебра Лi диференцiювань полiномiальної алгебри K[X] := K[x1, . . . , xn] над алгебраїчно замкненим полем K характеристики нуль. Пiдалгебра L ⊆ Wn(K) називається полiномiальною, якщо вона є пiдмодулем K[X]-модуля Wn(K). Доведено, що централiзатор кожного ненульового елемента з L є абелевим у випадку, коли L має ранг 1. Це дає можливiсть класифiкувати скiнченновимiрнi пiдалгебри полiномiальних алгебр Лi рангу 1.